135 The UK MS pregnancy register: baseline data from the first fifty enrolled patients. Issue 9 (12th August 2022) - Iyer, Priyanka; Craig, Elaine; Brex, Peter; Ford, Helen; Hughes, Stella; Middleton, Rod; Murray, Katy; Pearson, Owen; Rog, David; Dobson, Ruth
Abstract : Background: We present baseline data on the first 50 participants recruited to the UK MS Pregnancy Register. Methods: Data collected via questionnaires from consenting participants until 20th December 2021 were included. Results: 50 participants (all with relapsing remitting MS; mean age at diagnosis 28.0 years; mean age at recruitment 33.0 years) were included. Median EDSS was 2.5 (n=16). Gestation at recruitment ranged from 2 to 40 weeks. 78% had discussed their pregnancy in advance with their MS team. 90% of patients had ever taken DMT. Of the patients that stopped DMT (n=23), 16 reported stopping for pregnancy-related reasons. Of these, 39% stopped before pregnancy and 30% following conception. 15 women are continuing DMT during their current pregnancy, taking the following DMT: Glatiramer acetate (n=5), natalizumab (n=7), Peginterferon beta-1a (n=2), not recorded (n=1). In those with prior pregnancies, 61% (14/23) reported pregnancy loss with 1 case of a rare genetic condition in the baby. None of the prior pregnancy losses happened whilst on DMT. One participant reported previous PPH and foetal macrosomia and another reported previous pre-eclampsia. Conclusions: These results show that a patient-facing pregnancy MS registry is feasible and can collect previous adverse pregnancy outcomes. Future results will inform clinicians and women about the safety of DMT and adjunctive medication during pregnancy and postpartum.